Geographic arbitrariness?: County court variation in capital prosecution and sentencing in Pennsylvania - Ulmer, Jeffery T. (Criminology & public policy, 2020)
The death penalty remains one of the most controversial issues of criminal punishment not only because of racial/ethnic disparities, wrongful convictions, and inadequate defense representation but also because of the potential for geographic arbitrariness. The key empirical proposition embedded in the concept of geographic arbitrariness is that localities react to legally and procedurally equal capital cases in much different ways. This study assesses whether this key proposition is observed. We use data on 880 capital murder cases, nested in 18 counties in Pennsylvania from 2000 to 2010, to examine between-county differences in (a) prosecutors’ filing of specific aggravating circumstances, (b) prosecutors’ filings to seek the death penalty, (c) prosecutors’ decisions to retract a death filing, and (d) court (judges’ or juries’) decisions to impose the death penalty. First, we found that counties differed substantially in their decisions connected to the same statutory aggravators and murder characteristics. Second, propensity score weighting models demonstrated meaningful and sometimes huge differences between specific counties in prosecutorial decisions to file to seek the death penalty, and to retract those filings. We also found meaningful differences in the likelihood of defendants being sentenced to death across counties, although differences were not as large as those for the prosecutorial decisions. Little evidence exists that county partisan composition accounts for differences between counties in death penalty outcomes, and some limited evidence points to county size as a factor that shapes death penalty outcomes. Overall, however, results point to the idiosyncrasy of specific counties in their likelihood of exposing and sentencing defendants to the death penalty. Policy Implications The remedies most connected to this study's findings involve local prosecutorial discretion. A key suggestion would be to strengthen the narrowing function that is supposed to be performed by statutory definitions of aggravating factors. The number, breadth, and vagueness of aggravating factors give prosecutors more expansive discretion to select cases for exposure to the death penalty, as well as judges/juries wider grounds to potentially impose it. This discretion, in turn, allows for wide local variations in the interpretation and application of these aggravating factors. Constraining this discretion would necessitate reducing the number of aggravating factors and defining the remaining ones clearly and narrowly. Another possible remedy would be prosecutorial guidelines for the weighting and use of statutory aggravating factors. The very enterprise of capital punishment in the United States, however, may well have geographic arbitrariness inherently embedded in it. If so, there would be no practical way to eliminate geographic arbitrariness short of abolishing the death penalty.